De jure versus de facto institutions: trust, information, and collective efforts to manage the invasive mile-a-minute weed (Mikania micrantha). Issue 1 (March 2017) - Sullivan, Abigail; York, Abigail M.; White, Dave D.; Hall, Sharon J.; Yabiku, Scott T.
Differences in governance relationships and community efforts to remove an exotic, rapidly spreading invasive plant, the-mile-a-minute weed (Mikania micrantha), are explored in five case study community forests in the subtropical region of Chitwan, Nepal. An institutional analysis informs an examination of the de jure (formal) versus de facto (on the ground) institutions and actor relationships relevant to Mikania removal efforts. Contrary to the expectations set by the de jure situation, we find heterogeneous governance relationships and norms related to Mikania management across community forests. Content analysis of interview data illuminates reoccurring themes and their implications for social and ecological outcomes in the communities. Complex governance relationships and regular discussion of distrust of government and non-government officials help explain collective action efforts and management decisions. The content analysis suggests that Mikania is impacting people's daily lives but the degree of severity and the response to the disruption varies substantially and is affected by other problems experienced by community forest members. Our results indicate that understanding how the de facto, or on the ground situation, differs from the de jure institutions may be vital in structuring successful efforts to manage invasive species and understanding collective action problems related to other social-ecological threats. We present data-informed propositions about common pool resource management and invasive species. This study contributes to a better scientific understanding of how institutions mediate social-ecological challenges influencing common pool resources more broadly.